The Role of Parents in Using Digital Media to Stimulate Early Childhood Language Development - Budi Iskandar; Ernawulan Syaodih (SEA-CECCEP, 2022)
Digital media continues to be produced on a large scale. Digital media can be used with various functions; such as for entertainment, search many information, even has a good impact to various of early childhood development aspects. Digital media users are no longer only dominated by adults but also early childhood is the target of digital media marketing which is very popular these days. Therefore, it is necessary to know how to use digital media to stimulate children's language development. The writing of this article was carried out through a literature study where the study was carried out based on information obtained from various types of literature include scientific articles, books and other literary sources. The results of the analysis found that early childhood who had been exposed to digital media had good language development in both receptive and expressive language development. The type of digital media which often accessed by children are animated videos, audio books, fun language game applications and other educational applications. Language development stimulation occurs naturally with the parental control without a good structured planning, however parental guidance is needed to avoid negative effects for children such as immoral videos, excessive screen time that can damage children's eyes and addicted to the use of digital media for entertainment purposes.